Organizational models and forms of University sport – University of Zagreb in Croatia (No in EU) – University of Ljubljana in Slovenia (in EU) - Gošnik, Jelka; Kürner, Darja (2012)
The enrolment of students is increasing from year to year. Students are very satisfied with the subjects, their content and also with the system of exams. It is happening often that they choose two subjects in the same year. They are satisfied with the wide selection of practical activities. We see from the table that in the second year the number of students who passed the exam is bigger than the number of students enrolled. That is because some from the first year passed the exam later. The average grades are high which show that students like to learn. The subjects are also very popular with the foreign students in Erasmus or other exchange programmes.
Projekt MZOS
ENG